2014
DOI: 10.1002/tox.22095
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of methamidophos on paraoxonase 1 activity and on rat kidney and liver and ameliorating effects of alpha‐tocopherol

Abstract: The role of alpha-tocopherol on nephrotoxicity and hepatotoxicity induced by methamidophos (MT) was investigated in wistar rats. Animals were given via gavage, for four weeks, a low dose of MT (MT1), a high dose of MT (MT2), vitamin E (200 mg/kg of bw) or both MT2 plus vitamin E (Vit E) and control group was given distillate water. MT treatment resulted in a significant decrease in the body weight of MT2-treated group. Moreover, MT-treated groups had significantly lower butyrylcholinesterase (p < 0.01) and par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
(75 reference statements)
4
10
0
Order By: Relevance
“…Further supports to our discussion come from the work of Ahmad et al [47] and Araoud et al [48] who revealed that bendiocarp, carbofuran, …”
Section: Resultssupporting
confidence: 89%
“…Further supports to our discussion come from the work of Ahmad et al [47] and Araoud et al [48] who revealed that bendiocarp, carbofuran, …”
Section: Resultssupporting
confidence: 89%
“…Sublethal concentrations of methamidophos, phorate, and RPR-II seem to increase AcP and ALP in plasma and lower them in the liver tissue of animals (60,68,69). Similar findings have been reported for sub-chronic monocrotophos, methyl parathion, and dimethoate effects on ALP and AcP levels in plasma, but not in the liver, where they also increased (21,59).…”
Section: Biochemical Evidence Of Op Hepatotoxicitysupporting
confidence: 65%
“…Also, that the dosage and treatment duration Vitamin E varies across studies. Vitamin E has been used in a wide dose ranges from modest 100 IU/d[ 32 ] or 200 IU/d[ 33 34 ] to high doses such as 1200 IU/d[ 35 ] in various experiments. As antiepileptics are commonly weak oxidants, and their influence on oxidative stress have been commonly traced after long term intake of this agents, we believe that administration of a modest (400 IU/d) dose of Vitamin E could sufficiently compensate for their pro-oxidant activity.…”
Section: Discussionmentioning
confidence: 99%